Economic downturns and population mental health: research findings, gaps, challenges and priorities - Zivin, K. (2010)
Prior research suggests that the current global economic crisis may be negatively affecting population mental health. In that context, this paper has several goals: (1) to discuss theoretical and conceptual explanations for how and why economic downturns might negatively affect population mental health; (2) present an overview of the literature on the relationship between economic recessions and population mental health; (3) discuss the limitations of existing empirical work; and (4) highlight opportunities for improvements in both research and practice designed to mitigate any negative impact of economic declines on the mental health of populations. Research has consistently demonstrated that economic crises are negatively associated with population mental health. How economic downturns influence mental health should be considered in policies such as social protection programs that aim to promote recovery.